PPR - The Founding Conference (July 1994) - Parker, Ian (PINS-Psychology in Society, 2026)
Psychology Politics Resistance (PPR) held its founding conference in Manchester on 2 July 1994. This event, which brought together around 150 activists working in and against professional and academic psychology, is the culmination of national workshops and meetings over the last decade. Over three hundred people involved in psychology had already written in over the previous year supporting a founding statement for the new organization which declared its opposition to the many abuses of power in psychology, and support for initiatives to build a network of individuals and groups prepared to challenge these abuses. The five morning workshops on 2 July were designed to bridge the gap between the inside and the outside of the discipline and brought together psychologists and users of psychology services. Discussion in these workshops focussed on Institutional Abuse, the Law and Prisons, Eurocentrism and Racism, Sexuality, and Women and Psychology. This attention to different domains of abuse encouraged people to think of ways that the various existing resources could be connected in a network. The afternoon workshops looked at practical initiatives and future activities of PPR.